The Balochi Language and Languages in Iranian Balochistan - Jahani, Carina (Journal of the Middle East and Africa, 2013)
This article offers a broad introduction to the Balochi language and its dialects, as well as current trends in the official language policy both in Iran and in Pakistan. Other languages spoken in Iranian Balochistan are also presented, and the problems of and prospects for the continuing use of the Balochi language in Iran are discussed. From a historical point of view, Balochi is classified as a Northwestern Iranian language closely related to Kurdish, although it is spoken in the southeastern corner of the Iranian linguistic area. It is difficult to estimate the total number of Balochi speakers, but 10 million may serve as an approximation. The main dialect split is between Western, Southern, and Eastern Balochi. The fact that the Balochi speakers are separated into several countries with various official languages is another cause of dialect differentiation. Along with modernization came a secular education system and a nationalist discourse, first in British India and later in Iran. There is, however, no official use of Balochi as a language of administration or education. This poses a serious threat to the survival of the language beyond one or two more generations. Such a threat is, of course, even more imminent for the languages spoken by smaller communities in southeastern Iran, such as Jadgali, Brahui, Bashkardi, and Koroshi.